2020
DOI: 10.1124/dmd.120.000195
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase G9a Regulates Expression of Nuclear Receptors and Cytochrome P450 Enzymes in HepaRG Cells at Basal Level and in Fatty Acid Induced Steatosis

Abstract: Obesity and non-alcoholic fatty liver disease (NAFLD) affect expression and function of cytochrome P450 genes (P450s). The increased expression of inflammatory cytokines is a major driver of the down regulation of P450 expression in NAFLD. Decrease in P450 expression could potentially lead to drug-drug interaction, inefficient pharmacological effect of a drug or hepatotoxicity. An epigenetic modifier, a histone methyl transferase enzyme G9a, known to increase histone 3 lysine 9 (H3K9) methylation, is down regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The involvement of histone modifications in the regulation of CYPs has been proved by more and more studies (Yan et al, 2017;Wang et al, 2019a;Pande et al, 2020). For instance, H3K27ace was reported to be involved in HNF4A-mediated CYP2C9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of histone modifications in the regulation of CYPs has been proved by more and more studies (Yan et al, 2017;Wang et al, 2019a;Pande et al, 2020). For instance, H3K27ace was reported to be involved in HNF4A-mediated CYP2C9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes such as DNA methylation and histone modification are known to modulate gene expression changes and impact cellular function (28,29). As an epigenetic modifier, G9a has been documented to participate in many diseases (30,31) but its expression pattern and mechanism in Spn is largely unknown. This study investigated the mechanism of macrophage polarization mediated by histone methylase G9a in Spn mice, and eventually supported that G9a promoted M1 macrophage polarization by promoting H3K9me2 methylation in the FOXP1 promoter region, stimulating inflammation in Spn mice (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…The ChIP experiment showed the enrichment of H3K9me2 in the FOXP1 promoter region in RAW264.7 macrophages was decreased after G9a knockdown, and after addition of Bix01294 [a specific inhibitor of G9a (H3K9me2)] to cells, the enrichment of H3K9me2 in the FOXP1 promoter region was evidently inhibited. An epigenetic modifier, G9a is known to increase H3K9me2 (30,38), and RT-qPCR showed that FOXP1 transcription was increased clearly after G9a depletion. FOXP1 expression was also decreased in the Spn group but increased after G9a depletion.…”
Section: Discussionmentioning
confidence: 99%
“…1 In vitro Treatment with Recombinant FGF19 Protein. HepaRG cells were cultured as previously described (Hart et al, 2010;Pande et al, 2020). PHHs were from a cryopreserved pool (5 donors) of human hepatocytes (PHH8007A, IVAL, Columbia, MD).…”
Section: Methodsmentioning
confidence: 99%